Effect of surfactant on the dielectric and electrorheological properties of zinc borate/silicone oil dispersions - Gümüş, Ömer Yunus; Unal, Halil Ibrahim (Springer, 2019)
Zinc borate (ZB) particles dispersed in silicone oil (SO) at concentrations of phi = 5vol%-20vol% were subjected to dielectric analysis to elucidate their polarization strength, time, and mechanism. Results revealed that all virgin dispersions lacked polarization. Triton X-100, a non-ionic surfactant, was added to ZB/SO dispersions to enhance the polarizability of ZB particles. The addition of 1vol% Triton X-100 enhanced the polarizability of ZB/SO dispersions, and the 15vol%ZB/SO system provided the highest dielectric difference Delta epsilon ' (the difference in epsilon ' values at zero and infinite frequency, Delta epsilon ' = epsilon(0) - epsilon(221D)) of 3.64. The electrorheological (ER) activities of the ZB/SO/Triton-X dispersion system were determined through the ER response test, and viscoelastic behaviors were investigated via oscillation tests. A recoverable deformation of 36% under an applied electrical field strength of 1.5 kV/mm was detected through creep and creep recovery tests.
Keywords: zinc borate; electrorheological fluids; dielectric analysis; surfactant